HIGH-RESOLUTION CT CHEST FINDINGS IN RARE OCCUPATIONAL LUNG DISEASES – AN OVERVIEW - Dr.K.T.DHILEEPAN; DR.SHAIK FARID (International Journal of Pharma and Bio Sciences, 2015)
CT has an increasing role in the radiologic evaluation of occupational/ environmental lung disease. The high-resolution CT (HRCT) findings of siderosis, talcosis, berylliosis, calcicosis and hypersensitivity pneumonitis are described. The purpose of this article is to describe the high-resolution CT (HRCT) features of rare occupational lung diseases. The HRCT chest was done from June 2012 to June 2013 in 50 patients with occupational history related to the following diseases with a minimum of 5 years of occupational exposure with symptoms of cough with/ without sputum. No standardized quantification scheme is available for occupational lung diseases using CT.